Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi